Crystal Structure of the Extended-Spectrum β-Lactamase PER-2 and Insights into the Role of Specific Residues in the Interaction with β-Lactams and β-Lactamase Inhibitors - Ruggiero, Melina (2014)
PER-2 belongs to a small (7 members to date) group of extended-spectrum β-lactamases. It has 88% amino acid identity with PER-1 and both display high catalytic efficiencies towards most β-lactams. In this study, we determined the X-ray structure of PER-2 at 2.20 Å, and evaluated the possible role of several residues in the structure and activity towards β-lactams and mechanism-based inhibitors. PER-2 is defined by the presence of a singular trans bond between residues 166-167 that generates an inverted Ω loop, and an expanded fold of this domain that results in a wide active site cavity that allows for an efficient hydrolysis of antibiotics like the oxyimino-cephalosporins, and a series of exclusive interactions between residues not frequently involved in the stabilization of the active site in other class A β-lactamases. PER β-lactamases could be included within a cluster of evolutionary related enzymes harboring conserved residues Asp136 and Asn179. Other signature residues that define these enzymes seem to be Gln69, Arg220, Thr237, and probably Arg/Lys240A, with structurally important roles in the stabilization of the active site and proper orientation of catalytic water molecules, among others. We propose, supported by simulated models of PER-2 in combination with different β-lactams, the presence of a hydrogen-bond network connecting Ser70-Gln69-Water-Thr237-Arg220 that might be important for the proper activity and inhibition of the enzyme. Therefore, we could expect that mutations occurring in these positions will have impact in the overall hydrolytic behavior.